(untitled) (Global Journal of Science Frontier Research, 2016)
Through mathematical communication and discourse, teachers can foster student engagement and participation while focusing on the deep conceptual understanding called for in the Common Core mathematics standards. This qualitative study focuses on the importance of students’ mathematical communication (i.e. verbal and written) and discourse as they engage in problem solving, reasoning and proofs. Furthermore, the study demonstrates the development of mathematics language in order for students to better grasp the underlying mathematical concepts. The study finds that the discursive teaching strategies used by the classroom teacher can transform mathematics discourse from informal to formal. The study concludes discursive teaching strategies are viable option for secondary mathematics classrooms to effectively implement the recommendations of the Common Core State Standards for Mathematics (CCSSM).